2005
DOI: 10.1124/mol.104.010124
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cAMP and Calcium Signaling by Serotonin in Mouse Cumulus-Oocyte Complexes

Abstract: cAMP and intracellular Ca 2ϩ are important second messengers involved in mammalian follicular growth and oocyte meiotic maturation. We investigated the capacity of the neurohormone serotonin (5-hydroxytryptamine, 5-HT) to regulate intracellular cAMP and Ca 2ϩ in mouse oocytes and surrounding cumulus cells. On the basis of a reverse transcription-polymerase chain reaction study, 5-HT 7 receptor mRNA is expressed in cumulus cells, oocytes, and embryos up to the four-cell stage, and 5-HT 2A and 5-HT 2B receptor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…The same authors demonstrated that 5-HT caused a dose-dependent increase of cAMP and Ca 2+ levels in cumulus cells, presumably via 5-HT 7 and 5-HT 2A /5-HT 2B receptors, respectively. 146 Furthermore, 5-HT was shown to modulate gonadotropininduced steroid secretion of human granulosa cells in vitro. 147 In fish, the functional relationship of hypothalamus and pituitary regions varies between different species, but in general, the formation of neurological interfaces during phylogeny resulted in increased hypothalamic control of pituitary function.…”
Section: Role Of 5-ht In Reproductive Processesmentioning
confidence: 99%
“…The same authors demonstrated that 5-HT caused a dose-dependent increase of cAMP and Ca 2+ levels in cumulus cells, presumably via 5-HT 7 and 5-HT 2A /5-HT 2B receptors, respectively. 146 Furthermore, 5-HT was shown to modulate gonadotropininduced steroid secretion of human granulosa cells in vitro. 147 In fish, the functional relationship of hypothalamus and pituitary regions varies between different species, but in general, the formation of neurological interfaces during phylogeny resulted in increased hypothalamic control of pituitary function.…”
Section: Role Of 5-ht In Reproductive Processesmentioning
confidence: 99%
“…Next, we studied the effect of receptor stimulation on BMDC maturation. Immature and mature BMDCs were treated with the 5-HT 7 R agonist 5-carboxamidotryptamine maleate (5-CT; 10 µM) either alone or in combination with 10 µM of the highly selective 5-HT 7 R antagonist SB 269970 for 48 h. These concentrations were selected based on previously published data (Amireault and Dube, 2005;Crider et al, 2003;Kvachnina et al, 2005;Saitow et al, 2009). Quantitative analysis of flow cytometry data showed no difference in the number of immature and mature BMDCs after 5-HT 7 R stimulation (Fig.…”
Section: -Ht 7 R-mediated Signaling Does Not Affect Differentiation mentioning
confidence: 99%
“…Also using RT-PCR, it was found that mouse oocytes and pre-implantation embryos, up to the blastocyst stage, expressed 5-HT 1D but not 5-HT 1B or 5-HT 2C receptors (Vesela et al, 2003). Through both RT-PCR and immunological analyses, additional receptors, namely 5-HT 2A and 5-HT 2B , were discovered in mouse cumulus cells while 5-HT 7 receptor was expressed in both cumulus cells and oocytes as well as in embryos up to the four-cell stage, whereas 5-HT 2C , 5-HT 4 and 5-HT 6 receptors were not detected in any of these cells (Amireault and Dubé, 2005b). In contrast to mice, hamster oocytes appear to express the 5-HT 2A receptor but not the 5-HT 7 subtype (Amireault and Dubé, 2005b).…”
Section: Identification Of 5-ht Receptors In Ovarian Tissues and Cellsmentioning
confidence: 95%
“…Through both RT-PCR and immunological analyses, additional receptors, namely 5-HT 2A and 5-HT 2B , were discovered in mouse cumulus cells while 5-HT 7 receptor was expressed in both cumulus cells and oocytes as well as in embryos up to the four-cell stage, whereas 5-HT 2C , 5-HT 4 and 5-HT 6 receptors were not detected in any of these cells (Amireault and Dubé, 2005b). In contrast to mice, hamster oocytes appear to express the 5-HT 2A receptor but not the 5-HT 7 subtype (Amireault and Dubé, 2005b). As part of a study on expressed sequence tags amplified by PCR, human oocytes also appeared to express 5-HT 2A receptors (Neilson et al, 2000), even though more direct confirmation would be required, as well as for the reported possible expression of 5-HT 5A receptor in mouse oocytes detected by microarray analyses of RNA (Hinckley et al, 2005).…”
Section: Identification Of 5-ht Receptors In Ovarian Tissues and Cellsmentioning
confidence: 95%